Impact of a two-way short message service (SMS) to support maternally administered childhood mid-upper arm circumference monitoring and expand malnutrition screening in Kenya: the Mama Aweza trial protocol - Jennifer A Unger; Barbra A Richardson; Kirkby D Tickell; Mareme M Diakhate; Jeanne L Goodman; Arianna Rubin Means; Keshet Ronen; Carol Levin; Esther M Choo; Catherine Achieng; Mary Masheti; Benson O Singa; et al. (BMJ Open, 2020)
Introduction Over 52 million children under 5 years of age become wasted each year, but only 17% of these children receive treatment. Novel methods to identify and deliver treatment to malnourished children are necessary to achieve the sustainable development goals target for child health. Mobile health (mHealth) programmes may provide an opportunity to rapidly identify malnourished children in the community and link them to care.Methods and analysis This randomised controlled trial will recruit 1200 children aged 6–12 months at routine vaccine appointments in Migori and Homa Bay Counties, Kenya. Caregiver–infant dyads will be randomised to either a maternally administered malnutrition monitoring system (MAMMS) or standard of care (SOC). Study staff will train all caregivers to measure their child’s mid-upper arm circumference (MUAC). Caregivers in the MAMMS arm will be given two colour coded and graduated insertion MUAC tapes and be enrolled in a mHealth system that sends weekly short message service (SMS) messages prompting caregivers to measure and report their child’s MUAC by SMS. Caregivers in the SOC arm will receive routine monitoring by community health volunteers coupled with a quarterly visit from study staff to ensure adequate screening coverage. The primary outcome is identification of childhood malnutrition, defined as MUAC <12.5 cm, in the MAMMS arm compared with the SOC arm. Secondary outcomes will assess the accuracy of maternal versus health worker MUAC measurements and determinants of acute malnutrition among children 6–18 months of age. Finally, we will explore the acceptability, fidelity and feasibility of implementing the MAMMS within existing nutrition programmes.Ethics and dissemination The study was approved by review boards at the University of Washington and the Kenya Medical Research Institute. A data and safety monitoring board has been convened, and the results of the trial will be published in peer-reviewed scientific journals, presented at appropriate conferences and to key stakeholders.Trial registration number NCT03967015; Pre-results.